Экспериментальное исследование алгоритмов управления активным силовым фильтром с компенсацией мгновенной неэффективной мощности - Нос, Олег Викторович; Панкратов, Владимир Вячеславович (НТУ "ХПИ", 2013)
The report represents the research results of control strategy for a shunt active power filter using a quaternion algebra of the done in ERASIB Corp., which practical usage lets achieve harmonic waveform of three-phase currents consumed from the source in case of nonlinear unbalanced load with neutral wire.
Keywords: энергосбережение; трехфазная сеть; нелинейная несимметричная нагрузка; алгебра кватернионов